Glucose-6-Phosphate Dehydrogenase of Trypanosomatids: Characterization, Target Validation, and Drug Discovery. (4th April 2011) - Gupta, Shreedhara; Igoillo-Esteve, Mariana; Michels, Paul A. M.; Cordeiro, Artur T.
Abstract : In trypanosomatids, glucose-6-phosphate dehydrogenase (G6PDH), the first enzyme of the pentosephosphate pathway, is essential for the defense of the parasite against oxidative stress. Trypanosoma brucei, Trypanosoma cruzi, and Leishmania mexicana G6PDHs have been characterized. The parasites' G6PDHs contain a unique 37 amino acid long N-terminal extension that in T. cruzi seems to regulate the enzyme activity in a redox-state-dependent manner. T. brucei and T. cruzi G6PDHs, but not their Leishmania spp. counterpart, are inhibited, in an uncompetitive way, by steroids such as dehydroepiandrosterone and derivatives. The Trypanosoma enzymes are more susceptible to inhibition by these compounds than the human G6PDH. The steroids also effectively kill cultured trypanosomes but not Leishmania and are presently considered as promising leads for the development of new parasite-selective chemotherapeutic agents.